Ijarah sukuk in Nigeria: between compliance with shariah standards and practical challenges - Saleh, Abdulmajid Obaid Hasan; Bello, Aliyu Muhammad Bello (2025)
The issuance of sovereign Ijarah sukuk in Nigeria represents a significant example of applying Islamic finance instruments within a non-Arab, non-Islamic legal and economic environment. This study aims to outline the Shariah concept and characteristics of Ijarah sukuk, examine the extent to which the Nigerian experience complies with established Shariah standards, and identify the key institutional and legislative challenges hindering optimal implementation. The research adopts a descriptive-analytical methodology, drawing on classical jurisprudential sources, standards issued by recognized Shariah bodies, as well as official reports and recent academic studies. The findings reveal that the adopted structures in Nigerian issuances adhere to several core Shariah requirements, such as the existence of a genuine leased asset, distribution of returns as periodic rental payments, and the absence of explicit guarantees for principal or profit. Nevertheless, certain issues persist, including the absence of a comprehensive Shariah-compliant legal framework, limited specialized expertise, insufficient Shariah oversight, and concerns regarding the clarity of usufruct definition and risk-sharing mechanisms. The study recommends establishing an independent national Shariah board, enhancing legislative and regulatory frameworks, developing human capital, and expanding public awareness of Islamic finance to ensure the sustainability of the experience and its full alignment with Islamic principles.